Les grammaires de l’éducation critique aux médiasà l’épreuve du numérique - Irène PEREIRA (Tic & Société, 2017)
The article defines three grammars of critical media education that structure this field of research in continuity with other social spaces. It shows how a constructivist grammar dominates media education, within the French National Education system. It also highlights how, despite its positivist approach, the rationalist grammar of critical media education fails to escape from public controversy in the face of challenges posed by the flow of information on the Internet. Finally, the article highlights the revival of a third grammar, called “materialistic”, in particular through the renewal of the Frankfurt School of critical theory and an examination of the socio-ethical issues of media education using digital sociocriticism.